Effect of Clavibacter michiganensis subsp. sepedonicus on endogenous hydrogen peroxide levels and peroxidase activity in transgenic potato plants (Solanum tuberosum L.) expressing the gox gene - Filinova, N. V.; Ishchenko, A. A.; Kopytina, T. V.; Makarova, L. E. (Proceedings of Universities. Applied Chemistry and Biotechnology, 2025)
Higher levels of hydrogen peroxide (H 2 O 2 ) in plant tissues improve resistance to a variety of biotic and abiotic stressors. One of the key enzymes involved in the regulation of H 2 O 2 levels in plants is peroxidase. The present study was aimed at analyzing the level of endogenous H 2 O 2 , peroxidase activity, and its isoenzyme spectrum in the roots of in vitro Skarb cultivar and its transgenic lines expressing the Penicillium funiculosum glucose oxidase (gox) gene under normal conditions and with exposure to the phytopathogen Clavibacter michiganensis subsp. sepedonicus. The H 2 O 2 level of transgenic lines carrying the modified gox gene was shown to be significantly higher compared to the original cultivar and to increase further due to exposure to the phytopathogen. Under normal growth conditions, differences were observed in the spectrum of peroxidase isoforms in the transgenic lines and the original Skarb cultivar. Upon exposure to the phytopathogen, the spectrum of isoforms was significantly altered in the original Skarb cultivar and in the transgenic lines compared with the Skarb cultivar. The obtained data prove that the product of gox gene expression causes a high H 2 O 2 level due to glucose oxidation. High H 2 O 2 levels in transgenic lines presumably inactivate peroxidase. Exposure to the phytopathogen Clavibacter michiganensis subsp. sepedonicus is shown to increase peroxidase activity and change the isoenzyme composition in both control and transgenic lines.